Anti-hemolytic, hepatoprotective, and nephroprotective effects of black tea extract against Plasmodium berghei infected mice - Somrudee Nakinchat (2018)
© 2017, Walailak University. All rights reserved. Malarial associated hemolysis and liver and renal injuries are associated with mortality in adult patients with the severe form of this disease. Hence, we aimed to investigate the effects of black tea extract on hemolysis and liver and renal injuries induced by Plasmodium berghei ANKA infected ICR mice. Aqueous crude extract of black tea was prepared using the hot water method. For efficacy test in vivo, a standard 4-day test was carried out. Groups of ICR mice (5 mice of each) were inoculated intraperitoneally with 10 7 infected red blood cells of P. berghei ANKA. They were then treated orally by gavage with 100, 500, and 1,000 mg/kg of extract for 4 consecutive days. Parasitemia, hematocrit, alanine aminotransferase (ALT), and creatinine levels were measured. The results showed that black tea extract exerted dose-dependent anti-hemolysis and protection from liver and renal injuries induced by malaria, especially at doses of 500 and 1,000 mg/kg. However, 100 mg/kg of this extract did not show any effect. Additionally, there were no any toxicity in hemolysis or liver or renal injuries in normal mice treated with the highest dose of black tea extract. It can be concluded that aqueous crude extract of black tea presented anti-hemolytic, hepatoprotective, and nephroprotective activities against P. berghei ANKA infected mice.